Snowpit evidence of the 2011 Puyehue-Cordon Caulle (Chile) eruption in West Antarctica - Koffman, Bess; Kreutz, Karl (IEDA: US Antarctic Program Data Center, 2017)
We present several related datasets from a 2012 snow pit and a 2013 firn core collected near the WAIS Divide field camp in West Antarctica. The data include soluble ions (sodium and non-sea-salt sulfate) and dust particle concentrations, as well as major oxide geochemistry of tephra grains isolated from snow samples. Based on these data, we found evidence of deposition from the 2011 Puyehue Cordon-Caulle (Chile) volcanic eruption at WAIS Divide.